1998
DOI: 10.1073/pnas.95.3.1038
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of adenylylcyclase type VI proportionately increases β-adrenergic receptor-stimulated production of cAMP in neonatal rat cardiac myocytes

Abstract: Cellular content of cAMP generated by activation of adenylylcyclase (AC; EC 4.6.1.1) is a key determinant of functional responsiveness in the heart and other tissues. We have tested two hypotheses regarding the relationship between AC content and ␤-adrenergic receptor (␤AR)-mediated signal transduction in cardiac myocytes. First, that AC content limits adrenergic signal transduction, and, second, that increased AC, independent of (␤AR) number and G-protein content, yields a proportional increase in ␤AR-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
64
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 15 publications
9
64
3
Order By: Relevance
“…However, the degree of stimulation was unrelated to the receptor concentration, as the isoproterenol AC response was 10% above basal values in cortical regions, 50% in the lung, and 300% in the heart, despite the fact that bAR binding was similar in heart and cortical regions, and highest in the lung. This result is in keeping with previous observations that the degree of receptor coupling to downstream signaling elements is the key determinant of the net response (Gao et al, 1998(Gao et al, , 1999Navarro et al, 1991). Similarly, carbachol failed to inhibit AC despite high m 2 AChR concentrations, implying either that there is relatively poor coupling of these receptors to G i in the fetal brain or, alternatively, that stimulation by other mAChR subtypes offsets the inhibitory effect of m 2 AChRs (Gurwitz et al, 1994;Mangels and Gnegy, 1992;Migeon et al, 1995;Olianas and Onali, 1994); in keeping with the latter interpretation, there was significant stimulation by carbachol in the heart (po0.0001).…”
Section: Resultssupporting
confidence: 80%
“…However, the degree of stimulation was unrelated to the receptor concentration, as the isoproterenol AC response was 10% above basal values in cortical regions, 50% in the lung, and 300% in the heart, despite the fact that bAR binding was similar in heart and cortical regions, and highest in the lung. This result is in keeping with previous observations that the degree of receptor coupling to downstream signaling elements is the key determinant of the net response (Gao et al, 1998(Gao et al, , 1999Navarro et al, 1991). Similarly, carbachol failed to inhibit AC despite high m 2 AChR concentrations, implying either that there is relatively poor coupling of these receptors to G i in the fetal brain or, alternatively, that stimulation by other mAChR subtypes offsets the inhibitory effect of m 2 AChRs (Gurwitz et al, 1994;Mangels and Gnegy, 1992;Migeon et al, 1995;Olianas and Onali, 1994); in keeping with the latter interpretation, there was significant stimulation by carbachol in the heart (po0.0001).…”
Section: Resultssupporting
confidence: 80%
“…A similar lack of parallelism was seen for the other treatment paradigms and for the delayed-onset alterations determined in adulthood. These results are consistent with the view that the signaling proteins downstream from the receptors are the major determinants of functional responses (Gao et al 1998(Gao et al , 1999Navarro et al 1991), so evaluations of receptor binding alone may be entirely misleading for the interpretation of physiologic consequences.…”
Section: Discussionsupporting
confidence: 79%
“…Our general conclusion, then, is that the effects of CPF on AC signaling reflect actions exerted at the levels of the signaling components downstream from the receptors, the G-proteins and AC itself; therefore, the changes are heterologous, affecting all inputs that converge on this pathway. This inference is consistent with the view that development of G-protein-coupled receptor-mediated cell signaling is regulated primarily by mechanisms operating at the levels of G-proteins and AC (Gao et al 1998(Gao et al , 1999Gaudin et al 1995;Karoor et al 1996;Kohout and Lefkowitz 2003;Ostrom et al 2000;Slotkin et al 2003;Vatner et al 1998;Watts 2002). Finally, as in our previous studies with CPF (Aldridge et al 2003;Dam et al 2000;Garcia et al 2002;Icenogle et al, in press;Levin et al 2001Levin et al , 2002Slotkin et al 2001aSlotkin et al , 2002, we found distinct sex differences for exposures on GD17-20, PN1-4, or PN11-14 but not with the early gestational treatment (GD9-12).…”
Section: Discussionsupporting
confidence: 78%